How Useful Is CPI Price Data for Spatial Price Adjustment in Poverty Measurement? A Case from Ghana - Chen, Xiaomeng; Mungai, Rose; Nakamura, Shohei; Pearson, Thomas; Wambile, Ayago Esmubancha; Yoshida, Nobuo (World Bank, Washington, DC, 2020)
Measuring and comparing the levels of household welfare and poverty in a country require cost-of-living differences across regions to be properly adjusted. In measuring the spatial cost of living, the recent literature underscores the importance of detailed product quality information in the price data. Taking advantage of the price data availability in Ghana, this case study explores the Consumer Price Index price data as a source for spatial price measurement. It applies the country product dummy method to the Consumer Price Index price data and compares the results with other methods based on different price data. The empirical analysis indicates a potential bias in estimating spatial prices stemming from the lack of product quality information and, therefore, suggests the potential usefulness of the Consumer Price Index price data for spatial price adjustment in poverty analysis in low- and middle-income countries.